Chemical nanoscience and nanotechnology : new materials and modern techniques - Torrens, Francisco (Torrens Zaragoza); Haghi, A. K.; Chakraborty, Tanmoy (Oakville, ON ; Palm Bay, Florida : Apple Academic Press, 2020)
"This new volume provides a wealth of practical experience and research on new methodologies and important applications in chemical nanotechnology. It also includes small-scale nanotechnology related projects that have potential applications in several disciplines of chemistry and nanotechnology. In this book, contributions range from new methods to novel applications of existing methods to gain understanding of the material and/or structural behavior of new and advanced systems. The fast growing field of nanotechnology uses a variety of modern methods that give scientists the ability to design multifunctional materials and provide improved products. Understanding the world of nanotechnology is critically important because technology based on nanostructures promises to be hugely important economically. Topics cover computational methods in chemical engineering and chemoinformatics, studies of some of physico-chemical properties of several important nanoalloy clusters, the use of 3D reconstruction of nanofibrous membranes, nanotechnology research for green engineering and sustainability, nanofiltration and carbon nanotubes applications in water treatment, and much more. The information presented in Chemical Nanoscience and Nanotechnology: New Materials and Modern Techniques will be useful for scientists, researchers, faculty, and industry professionals working in chemical nanotechnology"--
OCLC-licensed vendor bibliographic record.
Keywords: Nanotechnology; Nanostructured materials; Nanoscience; Chemistry; SCIENCE / General; TECHNOLOGY / Engineering / Chemical & Biochemical; TECHNOLOGY / Material Science